Understanding language classroom contexts : the starting point for change - Wedell, Martin; Malderez, Angi, 1950- (London ; New York : Bloomsbury, 2013)
'Arguably the whole point of education is to effect change in what people know and are able to do. Globalization has contributed to a common perception worldwide of the need to introduce changes to the teaching and learning of languages. The success of many attempts to do so has been limited by insufficient consideration of implementation contexts. Understanding Language Classroom Contexts explores and illustrates how what happens in any (language) classroom is influenced by (and can be an influence on) the contexts in which it is situated. A clear understanding of these influences is thus the starting point for planning effective change. The book considers many visible and invisible features of the multiple layers of any context, and provides a framework for understanding the types of factors that may influence whether changes (planned by a teacher or externally initiated) are likely to be successful. The book will help teachers (and educational managers or change planners outside the classroom) to understand why their classrooms are as they are and so to make informed decisions about what can or cannot (or not easily) be changed, and suggests how any changes might be appropriately managed.'--Publisher's website.
Components of Contexts -- Exploring Culture -- Language and Languages in Education -- From Cultures to Methods -- From Methods to Approaches -- Teachers and Learners: As Part of and Creators of their Context -- Teachers and Learners: As'Products of their Context -- Schools and Classrooms: Physical and Cultural Contexts -- Planning and Implementing Classroom Change -- Conclusions: On Understanding Language Classroom Contexts and the Process of Change.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Foreign speakers; School improvement programs; English language -- Study and teaching -- Foreign speakers; School improvement programs